The Effect of Grain Boundaries on Schottky Diode Parameters (Baghdad Science Journal, 2004)
The activation energy and optical band gap of different regions (p-type) polysilicon have been measured. Both microscopic studies and current-voltage characteristics of diodes prepared on different surface regions were carried out. Comparison of diodes parameters and microscopic studies indicate that the type of angles between boundaries has a significant effect on diodes parameters while the boundary lengths per unit area has less effect. The mechanism of Al-interaction with grain boundaries and their intersecting points at different temperature were also studies. The X-ray fluorescence spectrometry has been used for detection of diffused A1%.